The Viking Eastern Baltic - Mägi, Marika, 1968- (Past imperfect (ARC Humanities Press), 2019)
This book demonstrates how communication networks over the Baltic Sea and further east were established and how they took different forms in the northern and the southern halves of the Eastern Baltic. Changes in archaeological evidence along relevant trade routes suggest that the inhabitants of present-day Finland and the Baltic States were more engaged in Viking eastern movement than is generally believed.